Biomechanical Analysis of the Effects of Bilateral Hinged Knee Bracing - Lee, Hangil; Ha, Dokyeong; Kang, Yeoun-Seung; Park, Hyung-Soon (Frontiers in Bioengineering and Biotechnology, 2016)
This research analyzed the effect of bilateral hinged knee braces on a healthy knee from a biomechanical frame in vivo. This was accomplished by fitting a knee brace with two customized wireless force/torque (F/T) sensors that could readily record force and torque during live motion, while the kinetics at the knee were computed using the inverse dynamics of the motion capture and force plate data. Four tasks to test the brace’s effects were drop vertical jumping, pivoting, stop vertical jumping, and cutting. The results showed that the hinges in the knee brace can absorb up to 18% of the force and 2.7 % of the torque at the knee during various athletic motions. Thus, the hinges demonstrated minimal effect in reducing the mechanical load on the knee. There were limitations concerning the consistency of the motions performed by the subjects during the trials and the influence of the other portions of the brace to evaluate the overall effectiveness of the brace as a whole. Future works may incorporate a fatigue protocol and injured subjects to better determine the effects of the brace. There is still a need for more research on the biomechanical influence of knee braces to develop safer and more effective products.